Pengaruh Kualitas Pelayanan, Sanksi Pajak, Biaya Kepatuhan Pajak, dan E-filling Pada Kepatuhan WPOP Non PNS - Wiryadana, Ida Bagus Komang; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p06, 2018)
Tax compliance is the behavior of a taxpayer in performing all tax obligations and use his taxation rights by sticking to the regulations of taxation legislation. The issue of tax compliance that has occurred in recent years is non-tax compliance. This non-compliance will result in tax evasion and embezzlement causing reduced tax revenue to the state coffers. The purpose of this study is to determine the effect of service quality, tax sanctions, tax compliance fees, and the application of e-filling on compliance reporting Individual Taxpayer (WPOP). This study was conducted in KPP Pratama Denpasar Timur. The number of samples is 100 WPOP non PNS, with nonprobability sampling method with purposive sampling technique. Data collection was done through interview, observation and questionnaire. The analytical technique used in this study is multiple linear regression. Based on the analysis result obtained service quality, taxation sanction, and application of e-filling have a positive effect on WPOP compliance, while tax compliance cost have negative effect on WPOP compliance. Keywords : service quality, tax sanction, compliance cost, and e-filling